Pemodelan Kualitas Air Sungai Sekitar Area Pertambangan Batubara di Kalimantan Menggunakan Software MIKE21 - Praditya Sigit Ardisty Sitogasa; Mufti Syahirul Alim Rudy (Prosiding ESEC, 2023)
The condition of water quality in Indonesia is one thing that really needs more attention to maintain its stability. This is because there are several inhibiting factors, one of which is the activity and/or business of an industry. PT X is an activity and/or business engaged in coal mining. As operational activities progress, the results of operational activities will be processed first in the WWTP and will later be discharged into the river body. The rivers in this activity and/or business area include the Bai River, Senibung River, Gulang-Gulang River, Sempayau River, and Rapak River. This research was conducted to determine the quality of the river water. The method used is to identify the water quality of the Bai River, Senibung River, Gulang-Gulang River, Sempayau River, and Rupak River using Mike21 software by modeling and simulating data in 2 scenarios, namely during the dry season and rainy season. The overall simulation results for average and minimum discharge conditions in the rainy and dry seasons show the distribution of TSS (mg/l) in the Gulang-Gulang River, which has the maximum concentration of TSS with a maximum distribution of 900 m, Rapak River 1600 m, River Sempayau is 1200 m away, Senibung River is 1700 m , Bai River is 1700 m.